2015
DOI: 10.2139/ssrn.2607520
|View full text |Cite
|
Sign up to set email alerts
|

Employment Effects of Foreign Direct Investment. New Evidence from Central and Eastern European Countries

Abstract: Tel: +33 (0)1 42 97 77 35, Fax: +33 (0)1 42 92 47 47. The views expressed herein are solely those of the authors and do not necessarily reflect those of Banque de France. Corresponding Author

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Though the impressive growth experienced in many of the SSA countries has been largely influenced by structural policies with macroeconomic adjustments, there are concerns over the effectiveness of such policies in ensuring more productive employment yields (Jude & Silaghi, 2016; Kamar et al, 2019). This is because, while these policies ensure consistent output expansion, they may be weak in enhancing distributional equity, sectoral interlinkages or productivity shifts in the necessary sectors that are expected to result in productive employment.…”
Section: Introductionmentioning
confidence: 99%
“…Though the impressive growth experienced in many of the SSA countries has been largely influenced by structural policies with macroeconomic adjustments, there are concerns over the effectiveness of such policies in ensuring more productive employment yields (Jude & Silaghi, 2016; Kamar et al, 2019). This is because, while these policies ensure consistent output expansion, they may be weak in enhancing distributional equity, sectoral interlinkages or productivity shifts in the necessary sectors that are expected to result in productive employment.…”
Section: Introductionmentioning
confidence: 99%
“…322-335). In the study by Jude and Silaghi (2015), it has been shown that the main determinant of employment dynamics in Central and Eastern European countries was the economic restructuring and the institutional change that accompanied progress in transition with traditional labor determinants, like output and wages, proved to be less important for different patterns of ownership.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, Jude and Silaghi (2015) suggest that there is a gap in the studies of the FDI effects on the employment indicators since major studies focus on productivity and wages (Aitken & Harrison, 1999, pp. 605-618;Girma et al, 2002, pp.…”
Section: Introductionmentioning
confidence: 99%
“…However, the evidence is more mixed for higher-income countries. Although manufacturing FDI in Sweden was associated with an increase in employment (Bandick and Karpaty 2011), FDI in central and eastern Europe led to job losses through competitive pressure and introduction of labor-saving technology (Jude and Silaghi 2015). For higher-income countries, FDI may decrease the number of jobs in the short term by introducing labor-saving technology, but it will likely increase job growth in the long term by enhancing labor productivity .…”
Section: Figure 33 Conceptual Framework: Fdi Has Varied Effects On Labor Market Outcomesmentioning
confidence: 99%